Mengidentifikasi Sumber Pencemaran Air Limbah Di Tempat Kerja - Adolf Liku, Adolf Liku; Mulya, Widya; Sari, Iin Pratama; Sipahutar, Merry K; Noeryanto, Noeryanto (EUNOIA, 2022)
Water pollution is a condition caused by the input of pollutant loads/waste wastes in the form of gases, dissolved materials, and particulates. Pollutants that enter water bodies can be carried out through the atmosphere, soil, runoff from agricultural land, domestic, urban, industrial waste, and others (Effendi, 2003). Pollution occurs when there are materials in the environment that cause unexpected changes, whether physical, chemical, or biological. The target that we will achieve related to the implementation of this community service is to provide knowledge for workers who work in the company about the importance of the dangers of water and waste pollution. In addition, the output of the results of this service will be made into articles to be published in community service journals, the application of controlling water and waste pollution in the workplace.